A Mixed-Method Study of Practitioners' Perspectives on Issues Related to EHR Medication Reconciliation at a Health System. Issue 2 (April 2019) - Rangachari, Pavani; Dellsperger, Kevin C.; Fallaw, David; Davis, Ian; Sumner, Michael; Ray, Walter; Fiedler, Shashana; Nguyen, Tran; Rethemeyer, R. Karl
Abstract : Background: In an effort to reduce medication discrepancies during transitions of care and improve accuracy of the patient's medication list, AU Health conducted a study to identify a comprehensive set of issues related to electronic health record ( EHR ) medication reconciliation ( MedRec ) from the perspective of practitioners directly involved in the EHR MedRec process. Methods: An exploratory mixed-method design was used. The 2-round study included 15 individual interviews, followed by a survey of 200 practitioners (ie, physicians, nurses, and pharmacists) based in the outpatient and inpatient medicine service at AU Health. Results: Thematic analysis of interview data identified 55 issue items related to EHR MedRec under 9 issue categories. The survey sought practitioners' importance rating of all issue items identified from interviews. A total of 127 (63%) survey responses were received. Factor analysis served to validate the following 6 of the 9 issue categories, all of which were rated "important" or higher (on average), by over 70% of all respondents: (1) care coordination (CCI); (2) patient education (PEI); (3) ownership and accountability (OAI); (4) processes-of-care (PCI); (5) IT-related (ITRI); and (6) workforce training (WTI). Significance testing of importance rating by professional affiliation revealed no statistically significant differences for CCI and PEI, and some statistically significant differences for OAI, PCI, ITRI, and WTI. Conclusion: There were 2 key gleanings from the issues related to EHR MedRec unearthed by this study: (1) there was an absence of shared understanding among practitioners, of the value of EHR MedRec in promoting patient safety, which contributed to workarounds, and suboptimal use of the EHR MedRec system; and (2) there was a sociotechnical dimension to many of the issues, creating an added layer of complexity. These gleanings, in turn, provide insights into best practices for managing both (1) clinical transitions of care in the EHR MedRec process and (2) sociotechnical challenges encountered in EHR MedRec implementation.